MASALAH ITIKAD BAIK DALAM PELAKSANAAN TUKAR TAMBAH BENDA BERGERAK JENIS KENDARAAN - Indah Nurlitasari (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT In working on an agreement both party should showing good gesture. But in some condition even when proper attention to good gesture has been practically shown by both party, the agreement still possibly in a deadlock. By this condition, more attention to good gesture should be paid so then the agreement will work satisfyingly. Each party come with their own motion and it will be impossible to insist the motion to the other. Both party should work on their ‘common ground’ the position where both party could agree to the term and condition then benefit of it. People who work on the agreement such as judge or lawyers should aware of this common ground and all factors to achieve the agreement for both party. There is a close tied between good gesture in agreement with theory of trust in agreement. Both articles commonly explain by the judge during judicial review. Both good gesture and appropriateness not only consider by the parties whose work on the agreement but also one factor and another during the work of the agreement. Finally the sale and purchase agreement of vehicle should held by paid more attention to good gesture and appropriateness, includes further consideration of norms and the rule of law.